Answer:
+ 9
+ 8
(This is an expression, not an equation so you can't find x with this expression. Equations have an = sign which can help isolate x on one side to find the value of x. This is the closest thing you could do for an answer for this expression.)
Explanation:
x(x+1)+(x+1)(x+2)+(x+2)(x+3)
= (x)(x) + (x)(1) + (x)(x) + (x)(2) + (1)(x) + (1)(2) + (x)(x) + (x)(3) + (2)(x) + (2)(3)
= x^2 + x + x^2 + 2x + x+ 2 + x^2 + 3x + 2x + 6
= (x^2+x^2+x^2) + (x+2x+x+3x+2x) + (2+6)
=
+ 9
+ 8
So first you expand the brackets and then you combine like terms.